Challenges for Sustained Observing and Forecasting Systems in the Mediterranean Sea - Tintoré, Joaquín; Pinardi, Nadia; Álvarez-Fanjul, Enrique; Aguiar, Eva; Álvarez-Berastegui, Diego; Bajo, Marco; Balbin, Rosa; Bozzano, Roberto; Nardelli, Bruno Buongiorno; Cardin, Vanessa; Casas, Benjamin; Charcos-Llorens, Miguel; et al. (Frontiers in Marine Science, 2019)
The Mediterranean community represented in this paper is the result of more than 30 years of EU & nationally funded coordination that has led to key contributions in science concepts and operational initiatives. Together with the establishment of operational services, the community has been coordinating with Universities, research centers, research infrastructures and private companies to implement advanced multi-platform and integrated observing and forecasting systems that facilitate the advancement of operational services, scientific achievements and mission-oriented innovation. As a result, the community has been able to respond to societal challenges and stakeholders needs, developing a variety of fit for purpose services such as the Copernicus Marine Service. The combination of state-of-the-art observations and forecasting provides new opportunities for downstream services in response to the needs of the heavily populated Mediterranean coastal areas and climate change. The real challenge for the next decade is to sustain ocean observations within the research community, to monitor the variability at small scales, e.g. mesoscale/submesoscale, to resolve the sub-basin/seasonal and inter-annual variability of the circulation and by this establish the decadal variability, understand and correct the model associated biases and to enhance model-data integration and ensemble forecasting for uncertainty estimation. Better knowledge and understanding of the Mediterranean variability will enable subsequent evaluation of the impacts and mitigation of human activities and climate change on the biodiversity and ecosystem functioning to underpin environmental assessments and decision support. Furthermore, the challenges are to extend the science based added value products to societal relevant downstream services and engage the communities to build initiatives that will contribute to UN SDG14 and the UN Decade of Ocean Science. The Mediterranean observing and forecasting capacity was built on the basis of community best practices in monitoring and modelling and could serve as basis for the development of the integrated global ocean observing system.